Surgical Innovations in Tracheal Reconstruction: A Review on Synthetic Material Fabrication - Usman Khalid; Petar Uchikov; Bozhidar Hristov; Krasimir Kraev; Maria Koleva-Ivanova; Maria Kraeva; Atanas Batashki; Daniela Taneva; Mladen Doykov; Angel Uchikov (Medicina, 2023)
Background and Objectives: The aim of this review is to explore the recent surgical innovations in tracheal reconstruction by evaluating the uses of synthetic material fabrication when dealing with tracheomalacia or stenotic pathologies, then discussing the challenges holding back these innovations. Materials and Methods: A targeted non-systematic review of published literature relating to tracheal reconstruction was performed within the PubMed database to help identify how synthetic materials are utilised to innovate tracheal reconstruction. Results: The advancements in 3D printing to aid synthetic material fabrication have unveiled promising alternatives to conventional approaches. Achieving successful tracheal reconstruction through this technology demands that the 3D models exhibit biocompatibility with neighbouring tracheal elements by encompassing vasculature, chondral foundation, and immunocompatibility. Tracheal reconstruction has employed grafts and scaffolds, showing a promising beginning in vivo. Concurrently, the integration of resorbable models and stem cell therapy serves to underscore their viability and application in the context of tracheal pathologies. Despite this, certain barriers hinder its advancement in surgery. The intricate tracheal structure has posed a challenge for researchers seeking novel approaches to support its growth and regeneration. Conclusions: The potential of synthetic material fabrication has shown promising outcomes in initial studies involving smaller animals. Yet, to fully realise the applicability of these innovative developments, research must progress toward clinical trials. These trials would ascertain the anatomical and physiological effects on the human body, enabling a thorough evaluation of post-operative outcomes and any potential complications linked to the materials or cells implanted in the trachea.